Effects of flexibility combined with plyometric exercises vs isolated plyometric or flexibility mode in adolescent male hurdlers - Racil, G.; Jlid, M. C.; Bouzid, M. S.; Sioud, R.; Khalifa, R.; Amri, M.; Gaied, S.; Coquart, J. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: This study aims to determine the effect of flexibility exercises combined with plyometrics in hurdles race, on physical fitness, motor skills (MS) and hip range of motion. METHODS: Thirty-four male hurdlers, (age=15.7±0.7 years, body mass=59.7±2.3 kg, height=170.8±2.4 cm) were randomly assigned to four independent groups. The (Gflex+plyo), the (Gplyo), the (Gflex) and a control group (Gcon). All participants performed different tests: a test of right and left hip flexion (RHF, LHF) and extension (RHE, LHE), squat jump (SJ), countermovement jump (CMJ), stiffness jump (STFJ) and three (MS) exercises (running, hopping and leaping). A 60-m sprint on the hurdles was also performed. RESULTS: The two-way analyses of covariance for repeated measures showed that Gflex+plyo increased significantly: the CMJ, performance on 60-m and showed higher performance in the between groups` comparison. The Gflex+plyo and Gflex showed the higher percentages of changes in flexibility (RHF: 3.2±1.3% and 3.0±2.1%; RHE: 6.4±2.4% and 9.4±4.1%, LHE: 8.4±3.4% and 7.8±4.3%, respectively). Gplyo increased significantly the LHF (3.9±1.4%) more than the other groups. In the between groups` comparison, Gplyo showed the higher percentage of change in STFJ (6.4±1.8%) and the Gflex+plyo showed the higher values in running and hopping (10.7±4.6% and 13.3±2.1%, respectively). CONCLUSIONS: Specific stretching exercises combined with plyometrics may be more beneficial than other training strategies in young sprint-hurdlers. This may better improve physical fitness, hip range of motion and may increase different level of skills which may better improve performance in hurdles race.